Cytokines and Other Mediators in Alopecia Areata - Stamatis Gregoriou; Dafni Papafragkaki; George Kontochristopoulos; Eustathios Rallis; Dimitrios Kalogeromitros; Dimitris Rigopoulos (Mediators of Inflammation)
Alopecia areata, a disease of the hair follicles with multifactorial etiology and a strong component of autoimmune origin, has been extensively studied as far as the role of several cytokines is concerned. So far, IFN-𝛾, interleukins, TNF-𝛼, are cytokines that are well known to play a major role in the pathogenesis of the disease, while several studies have shown that many more pathways exist. Among them, MIG, IP-10, BAFF, HLA antigens, MIG, as well as stress hormones are implicated in disease onset and activity. Within the scope of this paper, the authors attempt to shed light upon the complexity of alopecia areata underlying mechanisms and indicate pathways that may suggest future treatments.